Isolamento, seleção e identificação de fungos filamentosos produtores de enzimas de interesse para indústria de alimentos a partir de Moringa oleifera Lam., moringacea - Costa, Itana da Purificação (2008)
The moringa tree, Moringa oleifera L., is a tropical plant with many uses. Several studies have demonstrated the antimicrobial effect of the extract of moringa seed and flowers, but the literature lacks studies about the association of moringa with microorganisms such as endophytic fungi, able to live inside plant tissues and organs such as stems, leaves and roots of various plants without causing adverse effects to the host. The samples were aseptically collected, washed with sterile distilled water, followed by treatment with 70% alcohol for 1 min, sodium hypochlorite and 3% (v / v) for four minutes, 70% alcohol for 30 seconds, and three rinses in sterile distilled water. After disinfection proceeded isolation featuring four fragments (± 5mm) from the pod stems, leaf and root in petri plate containing culture medium PDA (Potato Dextrose Agar) and Sabouraud (AS). Was calculated, after the incubation period, the colonization rate for each sample (CR%) consisting of the total number of segments with one or more strains divided by the total number of threads used. The present study isolated 24 endophytic fungi of moringa, obtaining CR: 0% for root (regardless of medium), 20.83% for PDAL, ADP, 66.67% for PDAS, 33.33% for ASL and 87.5% for ASS. CR may vary with the composition of the medium, the plant species, geographical distribution, plant age, annual rainfall, the plant part used, among other factors. In this work, it was observed significant difference in CR between parts of the plant and not in relation to the culture medium. The isolates are represented by the genera: Aspergillus sp., Colletotrichum sp., Fusarium sp., Penicillium sp., Trichoderma sp., Geotrichum sp., Curvularia sp., Glomerella sp., and the bacterium Burkholderia gladioli. These microorganisms were tested for production of enzymes, amylase, protease, pectinase, lipase, and all isolates (100%) were active for at least one of the substrates tested, 23 (88.46%) showed pectinolytic activity and 19 (76, 17%) produced proteases. There were no detectable production of lipases and amylases by the method used. This study found 24 of the endophytes of Moringa oleifera Lam, with enzymatic capacity, being necessary to expand the study to better understand the distribution, colonization and interactions of microorganisms with moringa endophytes as well as verify their viability biotechnology (production of enzymes from other enzymes, pigments, flavorings, control pests on plants, etc..).